O uso de ferramentas tecnológicas em aulas de língua portuguesa: cultura maker, gamificação e multiletramentos. - Benvindo, Luciana Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
O presente trabalho apresenta reflexões acerca da utilização de ferramentas tecnológicas no ensino de Língua Portuguesa, bem como dos conceitos de cultura maker, gamificação e como esses contribuem para práticas multiletradas. O objetivo geral dessa pesquisa foi verificar possibilidades e refletir sobre diferentes maneiras de utilização de aparatos tecnológicos e da utilização da cultura maker no ensino da Língua Portuguesa, por meio do desenvolvimento de propostas de ação baseadas no conceito de cultura maker, gamificação e multiletramento. Para o desenvolvimento dessa proposta, nos embasamos na metodologia de pesquisa qualitativa de caráter exploratório, buscando compreender a necessidade da utilização de diferentes recursos em sala de aula, mediante revisão bibliográfica e análise das propostas de trabalho. Nossa base teórica esteve atrelada a livros e artigos publicados em periódicos nacionais e internacionais a partir de descritores como tecnologia no ambiente escolar, cultura maker, gamificação, multimodalidades e multiletramentos. Nesse ínterim, serviram como base os estudos de autores como Borges (2013) Gavassa (2015) e Vygotsky (1999), Dionísio (2011), Rojo (2012, 2015). A experiência com a pesquisa nos mostrou que há inúmeras possibilidades de práticas que podem ser realizadas em sala de aula com o uso de tecnologias, desde que haja intencionalidade, valorização dos saberes pré-existentes e, ainda, coletividade.

The present work presents reflections about the use of technological tools in the teaching of Portuguese Language, as well as the concepts of maker culture and gamification, and how these elements contribute to the teaching and learning process, favoring the taste for reading. Because we are inserted in technological spaces, we observe the need for this research, focusing on the use of these resources that are available in the students' daily life and understanding their possible use as a didactic tool. The general objective of this research was to verify the possibility of developing work with the Portuguese Language, focusing on reading and text interpretation activities, through the development of proposals for action based on the concept of maker, gamification and multiliteracies culture mediated by technology and also to investigate and reflect on different ways of using technological devices and the use of the maker culture in the teaching of the Portuguese Language. For the development of this proposal, we used as research methodology the exploratory qualitative research, seeking to understand the need to use different resources in the classroom, through a bibliographical review and analysis of the work proposals. The bibliographic review was carried out through books and articles published in national and international journals from descriptors such as technology in the school environment, culture maker, gamification, multimodalities and multiliteracies. In the meantime, studies by authors such as Borges (2013) Gavassa (2015) and Vygotsky (1999), Dionísio (2011), Rojo (2012, 2015) were used as basis. Because we believe in the importance of a work on this subject, it was possible to consider that there are many possibilities of works with multiliteracies and technologies in the classroom and that their development can be realized, since they are involved in intentionality, valorization of the preexisting knowledge and still collectivity.
The use of technological tools in classes of Portuguese Language: maker culture, gamification and multiliteracies
Keywords: cultura maker; ensino e aprendizagem de Língua Portuguesa; ferramentas tecnológicas; multiletramentos